Land Cover Change using GIS and RS Techniques of the Padma River Floodplain in the Three Adjacent Districts in Bangladesh (Jagannath University Journal of Science, 2024)
Bangladesh is a nation characterized by its reliance on river systems for various aspects of its socio-economic and geographical features. The region experiences a significant number of natural disasters every year as a result of the existence of the river. The region undergoes regular riverbank erosion as a result of the continuous changing of river channels. This study aimed to assess the changing of the Padma River and its impact on land use and land cover in the three adjacent districts of Munshiganj, Madaripur, and Shariatpur. Geographic Information System (GIS) along with remote sensing (RS) techniques were employed to analyze data collected between 1988 and 2023. Best results in detecting land-use/land-cover type and identifying erosional impact were achieved using K-means cluster unsupervised image classification. The accuracy of image preprocessing and classification was separately evaluated using the kappa coefficient. For the years 1988, 1993, 1998, 2003, 2008, 2013, 2017, and 2023, the findings indicated an overall accuracy of 86.36%, 83.32%, 87.1%, 85.43%, 87.3%, 87.92%, 88.42%, 90.06% and a kappa coefficient of 83.02%, 83.32%, 86.66%,85.37%, 87.78%, 87.29%, 87.91%, 86.59% respectively. Arable land accounted for 56.40 percent of the overall accreted land area (26340.06 ha), whereas cropland accounted for just 5.99 percent (2798.10 ha) based on long-term river channel migration results. In 35 years, arable land (23661.21 ha) suffered the most erosion (55.42%), followed by inland water (3351.53 ha), which suffered the least (7.15%). The implementation of an embankment inside the research area is proposed as a potentially efficacious strategy for mitigating riverbank erosion in this particular region. The government may implement long-term rehabilitation projects to support individuals who have been displaced by bank erosion and are now landless.Jagannath University Journal of Science, Volume 10, Number I, Jun. 2023, pp. 43-54